Numerical integration based on linear Legendre multi wavelets - Abdul Sathar, Mohammad Hasan; Rasedee, Ahmad Fadly Nurullah; Ahmedov, Anvarjon A.; Asbullah, Muhammad Asyraf (Institute of Physics Publishing, 2018)
In the present work, a new direct computational method for solving definite integrals based on linear Legendre multi wavelets is introduced. This approach is an improvement of previous methods which are based on Haar wavelets functions. An algorithm using properties of the linear Legendre multi wavelets is developed in order to find numerical approximations for double, triple and improper integrals. The main advantage of this method is its efficiency and simple applicability. To validate the algorithm, numerical experiments are conducted to illustrate the accuracy of the method.